Promoting the dignity and worth of all people: The privilege of social work. (November 2018) - Henrickson, Mark
The Dame Eileen Younghusband Lecture is presented every two years at the joint world conferences of international social work. In 2016 it was presented in Seoul and was based on the conference theme 'promoting the dignity and worth of people'. The lecture includes a review of heroes, legal, political and social successes, and challenges for sexual and gender minorities around the world. It challenges the binary of gender and sexuality. The privilege of social work is to choose either to challenge or to reproduce oppression based on sexuality and gender, and protect the dignity and worth of all peoples.